IBM system z9 109 technical introduction - Ogden, Bill (IBM redbooks., 2005)
This IBM Redbook introduces the IBM System z9 109 (z9-109), which offers a continuation of the IBM scalable mainframe servers. The z9-109 server is based on z/Architecture and provides extensions to the architecture. In addition to increased performance and expansion options, particular emphasis has been placed on the integration of the z9-109 into a complete system and software environment.